2011
DOI: 10.1109/tuffc.2011.2090
|View full text |Cite
|
Sign up to set email alerts
|

Time-delay spectrometry measurement of magnitude and phase of hydrophone response

Abstract: A method based on time-delay spectrometry (TDS) was developed for measuring both magnitude and phase response of a hydrophone. The method was tested on several types of hydrophones used in medical ultrasound exposimetry over the range from 5 to 18 MHz. These included polyvinylidene fluoride (PVDF) spot-poled membrane, needle, and capsule designs. One needle hydrophone was designed for high-intensity focused ultrasound (HIFU) applications. The average reproducibility (after repositioning the hydrophone) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 18 publications
0
33
0
Order By: Relevance
“…The complex sensitivity of the fiber optic hydrophone was obtained from the Fourier transform of the impulse response provided by the manufacturer. Complex sensitivities for the three needle hydrophones were measured using a digital time-delay spectrometry (TDS) system previously described [27, 53]. (There are many methods for measuring sensitivity magnitude but fewer methods for measuring sensitivity phase [5357], with some TDS methods extending to frequencies as high as 40 MHz [27, 56] and a nonlinear method providing phase measurements at harmonic frequencies up to 100 MHz [55] Some methods have shown that common hydrophone measurement systems can be accurately modeled as minimum phase systems [27, 53, 56]. )…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The complex sensitivity of the fiber optic hydrophone was obtained from the Fourier transform of the impulse response provided by the manufacturer. Complex sensitivities for the three needle hydrophones were measured using a digital time-delay spectrometry (TDS) system previously described [27, 53]. (There are many methods for measuring sensitivity magnitude but fewer methods for measuring sensitivity phase [5357], with some TDS methods extending to frequencies as high as 40 MHz [27, 56] and a nonlinear method providing phase measurements at harmonic frequencies up to 100 MHz [55] Some methods have shown that common hydrophone measurement systems can be accurately modeled as minimum phase systems [27, 53, 56]. )…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Unlike membrane hydrophones, they do not present big planar interfaces that can produce reflections that possibly could interfere with measurements, especially for long-pulse or continuous-wave operation. Needle hydrophones are often used for cavitation detection [1], transcranial ultrasound system characterization [29], high-intensity therapeutic ultrasound system characterization [1012], gene-delivery system characterization [13], high-frequency transducer characterization [14], and other medical applications [15, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…The complex pressure reciprocity parameter, J, must be calculated for a small rigid-walled cavity in order to obtain the hydrophone sensitivity from the voltage and current measurements in (8). The crux of the primary calibration is that the reciprocity parameter is derived in terms of the acoustic properties of the fluid medium.…”
Section: Reciprocity Parametermentioning
confidence: 99%
“…The type H48 reference is used well below it first resonance, but the low end of the frequency range can be affected by the low-frequency cutoff, problematic when secondary references are needed to measure frequencies below 5 Hz. Extending the coupler reciprocity calibration measurement to include phase is important to provide traceability for secondary references and to reduce Driven by the needs of the ultrasound community, calibrations can now include phase measurement using non-linear acoustic wave propagation [5,6], time-delay spectrometry [7,8], and pulse excitation [9,10] methods. Lower frequency, underwater calibrations are also using phase [11].…”
Section: Introductionmentioning
confidence: 99%